De-privatisation and remunicipalisation of urban services through the pendulum swing: Evidence from Germany - Weber, Gabriel; Cabras, Ignazio; Frahm, Lars-Gunnar (Journal of Cleaner Production, 2019)
This paper explores and examines the distribution of environmental conflicts in Germany between 1985 and 2015, analysing the main causes for environmental conflicts related to privatisation and de-privatisation processes of urban services in 80 German cities. Using information collected via means of a Delphi Method based on focus groups with experts, we identify 90 cases of large-scale privatisation initiatives involving urban services occurred in different fields within the period considered. In 38 cases, privatisation was reversed due to initiatives undertaken by environmental justice organisations and other local grassroots groups promoting de-privatisation and re-municipalisation. In another 30 cases, privatisation was prevented as a result of these initiatives. Findings from our analysis indicate that de-privatisation initiatives and potential conflicts related to them are frequently driven by grassroots organisations promoting the provision of commons-based urban services. Our findings also suggest that privatising services in the energy, water supply and waste management sectors is likely to negatively affect the quality of service supply and increasing prices for urban residents. Image 1 • This paper explores ecological conflicts in Germany by using comparative analysis, statistics, and political ecology. • It investigates the main causes for conflicts related to privatisation and de-privatisation of urban services. • With a Delphi Method and focus groups with experts, we identify 90 cases of large-scale privatisation. • 38 initiatives of de-privatisation are identified, many driven by grassroots organizations reclaiming the concept of commons. • De-privatisation initiatives indicate a pendulum swing towards more socially controlled production.
Keywords: Delphi method; Germany; Polanyi's pendulum; city dwellers; environmental justice; pendulums; political ecology; privatisation and de-privatisation; remunicipalisation; services and utilities; sustainable cities; urban areas; water supply management

Islam, entrepreneurship, and embeddedness - Tok, M. Evren; Kaminski, Joseph Jon (Thunderbird International Business Review, 2019)
This study centers on the premise that entrepreneurship is an embedded process. Although "the entrepreneur" is inherently an "individual," entrepreneurship can never be fully disembedded from the more general social settings within which any business venture is situated. An Islamic‐based economic discursive framework should be cognizant of the different forms of sociality, spatiality, and community as well as the various norms, codes, and symbols that define society more generally. The work of Karl Polanyi on embeddedness is engaged and juxtaposed with Islam's understanding of the ideal mode of economic discursive practices. Islamic economic models and Polanyi are both critical of the corrosive effects of unbridled capitalism and individualism that ultimately lead to reification and exploitation. The conclusion recommends more small‐N case studies by researchers and entrepreneurial educational materials that emphasize the importance of networks and local embeddedness.
Keywords: Islam; POLANYI, Karl, 1886-1964; discursive practices; economic models; entrepreneurship; teacher researchers

State Capitalism Revisited: A Review of Emergent Forms and Developments - Dolfsma, Wilfred; Grosman, Anna (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
Even when the neoliberal ideology of the free market was more dominant than it now is, the state was involved in economic activities that could be undertaken by private firms. State capitalism takes increasingly diverse forms, including beyond direct, partial or even indirect ownership. This paper briefly reviews some of these forms without claiming to be exhaustive as the shape state capitalism takes differs widely across the institutionalized contexts of countries. We assess state capitalism using Polanyi's double movement framework and argue that this framework needs adaptation to novel forms of state capitalism that include, e.g., state-owned multinationals and sovereign wealth funds.
Keywords: SOMNCs; capitalism; double movement; economic development; economic systems; international relations; investments; profit; sovereign wealth funds; state capitalism; state-owned enterprises

Financialization, Class Interests, and Karl Polanyi's Protective Response - Zalewski, David A. (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
Many observers expected a stronger countermovement against neoliberalism following the Great Recession. This article argues that such a protective response failed to materialize because the financialization process has aligned the preferences of labor and rentier classes. The result has been weaker support in democracies for expansionary monetary and fiscal policies during the early stages of recessions, which further lowers aggregate spending by increasing uncertainty. Thus, reversing the culture of financialization may be a necessary condition for preventing and responding to financial crises.
Keywords: Polanyi, Karl, 1886-1964; business development; double movement; economic development; economic policy; financial crises; financialization; macroeconomic policy; monetary policy

Karl Polanyi on Strategy: The Effects of Culture, Morality and Double-Movements on Embedded Strategy - Faulconbridge, James; Muzio, Daniel (Social Science Research Network, 2019)
Karl Polanyi is arguably one of the most significant economic sociologists. At first glance the links between Polanyi’s ideas about markets, society and institutions and strategy may not be obvious. However, there is a hereto unrecognised link between recent writing about institutions and strategy and Polanyi’s work. In this paper we, therefore, chart how, when recognised, these links reveal that Karl Polanyi’s work might provide new ways of thinking about strategy. Our over-riding claim is that Polanyi’s ideas reveal the importance of considering how strategies are defined, responded to, and ultimately rendered effective or ineffective in ways that are determined by relationships between markets, the state and society. It is thus crucial to understand strategy as embedded, this implying consideration of a strategy’s legitimacy in economy and society as an instituted process at any particular place and time. This also implies wider political questions about strategy in society and the extent to which strategists need to be aware of the ‘double movement’ Polanyi discusses and ensure strategies serve the interests of society as well as those of the market. KM: from forthcoming book "Critical perspectives on Accounting"
Keywords: double movement; embeddedness; professional services; strategy

A moral householding perspective on the sharing economy - Laamanen, Mikko; Wahlen, Stefan; Lorek, Sylvia (Journal of Cleaner Production, 2018)
Abstract In this paper, we scrutinise the sharing economy from a moral householding perspective and evaluate the moral justifications for a sustainable form of the sharing economy. We consider the emergence of normative moral justifications through householding practices that rest on local mobilisation of people in defence of communities and commitments against the adverse impacts of neoliberal market capitalism. Our perspective draws on Karl Polanyi's conceptualisation of householding, that is, autarchic, communistic provision in a closed community. Using timebanking as an example, we illustrate how a moral sharing economy can be mobilised in collective battles against the current neoliberal system of economic crisis. We contribute to the amassing sharing economy literature emphasising a central, yet missing element of the current discourse: householding as practices creating self-sufficiency and autonomy as well as combining both kin and stranger.
Keywords: financial crises; householding; households; market capitalization; mobilisation; moral economy; sharing economy; sustainable development; timebanking

Capabilities Accumulation and Development: What History Tells the Theory - Dosi, Giovanni; Yu, Xiaodan (2018)
In this contribution we offer a broad overview of the technological, institutional and policy dynamics associated with the great transformation--borrowing Karl Polanyi (1944) expression--leading from traditional, mostly rural, economies to economies driven by industrial activities (and nowadays also advanced services), able to systematically learn how to implement and eventually how to generate new ways of producing and new products under conditions of dynamic increasing returns. Such a 'great transformation' entails a major process of accumulation of knowledge and capabilities, both at the levels of individuals and organizations. Certainly, part of such capabilities builds on education and formally acquired skills (what in the economists' jargon often goes under the heading of 'human capital'). However, at least equally important, capabilities have to do with the problem-solving knowledge embodied in organizations--concerning e.g. production technologies, the technical and social division of labor, labor relations as well as 'dynamic capabilities' of search and learning. In turn, the rates and directions of knowledge accumulation during the catch-up process and the ensuing effects upon the patterns of production and trade are shaped by the economic and institutional framework in which such processes are embedded.
Keywords: Great Transformation, The (Book); capability accumulation; catching-up; development; innovation

Market fundamentalism in the age of 'haute finance': The enclosing of policy space in 'emerging' India - Lakshminarayan, Srivatsan (Ephemera: Theory & Politics in Organization, 2017)
The rise of the Emerging Market is a remarkable exemplar of an idea that originated and was socialized in Western financial markets during the 1980s. It has since gained rapid, wider normative status with respect to a particular set of beliefs that motivate policy choices on macroeconomic management, economic development and financial sector reforms in developing and less developed countries. I draw on the Polanyian notion of commodification and recent extensions to his scholarship in the realm of ideas that seek to explicate processes through which the dominant ideal of the self-regulating market is justified as fundamental to the organization of society. Against the backdrop of globally mobile capital, I critique the prevalence of a particular ideology of emergence in which commodified geography and commodified finance interact to shape policy. In this process, evaluative talk plays a key role in legitimizing the expectations of global capital and overcoming inherent contradictions through the rhetoric of non-crises. I thus highlight the ascendance of a narrow and instrumentally economic understanding of emergence in contemporary, post reform India as is asserted in conventional policy discourse. I conclude by remarking on the significant constriction of ideational space for the consideration of alternative, historically informed approaches to social and economic development. The legacy of Karl Polanyi serves as a prophetic reminder for the consequences of such constriction.
Keywords: India; commodification; economic development; emerging markets; haute finance; macroeconomics

Polanyi and Political Consumption: A Modern Theoretical Application of the Double Movement - Frank, Phillip M. (Society for Marketing Advances Proceedings, 2016)
There has been an increase in literature on a growing field recently termed, "Political Consumption" (Baumann et al., 2015). Political consumption is defined as the choice or avoidance of products or brands with the aim of changing ethically or politically objectionable institutional or market practices (Shah et al., 2007). The following paper posits a theoretical model for the conceptualization of political consumption. Specifically, the author presents Karl Polanyi and his "Double Movement" as the underpinning theoretical conceptualization of Political consumption. The author also proposes empirical research to test such a theoretical model.
Keywords: brand choice; branding (Marketing); consumer behavior; consumption (economics); double movement; political consumption; product management

Economic Exchange: Interdisciplinary Conceptualizations for Management Applications - Das, Roshni (Vilakshan: The XIMB Journal of Management, 2016)
The concept of 'Economic Exchange', taken in the neoclassical economics sense, has traditionally yielded a unilateral direction for business and management studies, that of profit maximization. This paper argues that, the same, when conceptualized from a sociological and anthropological point of view in particular, taking theorization by Polanyi (1946), Weber (1978) and Zafirovski (2001) into cognizance, can generate many alternative and interesting directions. Illustrations for the same have been provided in the form of management applications. Some controversies in the lifecycle of the concept have been noted such as that of the 'rational' man or Homo Economicus, which eventually led to the emergence of socio-economics and the consequential paradigmatic realignments among scholars, as a rebuttal to the dominant paradox. We undertake a conceptual exploration and synthesis of the relevant trans-disciplinary literature. Future implications for discursive research in management are discussed.
Keywords: WEBER, Max, 1864-1920; ZAFIROVSKI, M.; anthropology; economic exchange; economic man; homo economics; homo economicus; industrial management; methodological indivisualism; profit maximization; socioeconomics

Re-embedding Financial Stakes within Ethical and Social Values in Socially Responsible Investing (SRI) - Revelli, Christophe (Research in International Business and Finance, 2016)
The aim of this study is to understand how the definition of ethics in finance has steered socially responsible investing (SRI) towards a financial approach where ethics is guided by finance. Following a critical perspective of historical and modern SRI, we advocate a reconceptualization of the SRI paradigm through a framework that re-embeds finance in ethical and social values according to Polanyi's theory of embeddedness. To conclude, we propose an SRI model where impact measurement and extra-financial performance guide investments.
Keywords: economic anthropology; economic sociology; embeddedness; general financial markets: general (includes measurement and data) G10; social and economic stratification; social finance; socially responsible investing

Quality Work and the Moral Economy of European Employment Policy - Bolton, Sharon; Laaser, Knut; Mcguire, Darren (JCMS: Journal of Common Market Studies, 2016)
Following a decade of radical economic and workplace restructuring, it is important to understand how state employment policies support or deny human flourishing. This article utilizes a realist document analysis approach and reviews European employment policy through a moral economy lens. It fuses different moral economy approaches, drawing together the work of Karl Polanyi and Andrew Sayer a multi-layered conceptual lens is offered that explores the tensions between a commodification of labour and human needs. A dominant market ideology is revealed, highlighting how quality work has been subsumed by the flexicurity agenda in the EU.
Keywords: European employment policy; dignity; employment; flexicurity; management studies; moral economy; quality work

Book Review Essay: The Environmental Crisis and Its Capitalist Roots: Reading Naomi Klein with Karl Polanyi*—Naomi Klein: This Changes Everything: Capitalism vs. the Climate - Adler, Paul S. (Administrative Science Quarterly, 2015)
An essay is presented on the relationship between climate change and capitalism, offering a reading of the argument in "This Changes Everything: Capitalism vs. the Climate" by Naomi Klein through the lens of the analysis in "The Great Transformation" by Karl Polanyi. The author suggests that Klein's argument is not clear on whether capitalism in any form or only the current, neoliberal version of capitalism is incompatible with effective action to address the problem of climate change. Topics include environmental externalities and policies addressing them, the environmental record of corporations, and the theory of the self-regulating market.
Keywords: Great Transformation, The (Book); KLEIN, Naomi; This Changes Everything (Book); business enterprises & the environment; capitalism; climatic changes; economic aspects; environmental policy; externalities

Corporate Power and Responsible Capitalism?: Towards Social Accountability - Jones, Bryn (Edward Elgar Publishing, 2015)
In this important book, Bryn Jones uses insights from political economy, historical analysis and sociological concepts of the corporation, as a socially disembedded but political actor, to address concerns over the over-reach of Anglo-Saxon corporation KM -- on page 6: "Following Karl Polanyi, I argue that ST/EM firms have outgrown and threaten to dominate, envelop and even undermine, some of the social and political institutions on which a sustainable market economy depends. Any rebalancing of the relationship between corporations and the rest of society must therefore interrogate the nature of the relationship between market organisations, such as firms, and the social institutions to which they are linked.
Keywords: ST/EM corporations; business & economics; business ethics; business systems; corporate governance; disembedding; executive managed corporations; industrial management; management; management science; organizational behavior; share-traded corporations; social embedding

Mobilizing the depths of the market: Motivation research and the making of the disembedded consumer - Schwarzkopf, Stefan (Marketing Theory, 2015)
Twentieth-century consumer society was characterized by a process of disembedding as described by Karl Polanyi in The Great Transformation (2001 [1944]). The Austro-American consumer researcher Ernest Dichter played a key role in preparing the ideological framework necessary for this process to succeed. In order to assess Dichter’s role and that of psychoanalytic motivation research in general in the creation of the idea of the disembedded consumer, this article presents an analysis of Dichter’s unpublished consumer research reports ranging across different countries and industries between 1939 and 1973. Through content analysis and historical contextualization, I show that Ernest Dichter in particular and psychoanalytic motivation research in general were instrumental in removing from market relationships the invisible hand of social norms. The case of the consumer psychoanalyst Ernest Dichter thus provides new insights into the sociocultural mechanisms by which theorizing in consumer research can influence the objects of its theorizing.
Keywords: DICHTER, Ernest; consumer research; disembedding; interpersonal relations; market society; marketing; motivation research; pleasure principle; psychoanalysis; therapeutic ethos

Embracing ambiguity - lessons from the study of corporate social responsibility throughout the rise and decline of the modern welfare state - Schneider, Anselm (Business Ethics: A European Review, 2014)
In the work of Karl Polanyi, the negative effects of a self-regulating market economy are described as being limited by societal forces such as the policies of the welfare state. With the decline of the modern welfare state since the late 1970s, social activities of business firms are increasingly regarded as an important complement to or even as a substitute for welfare state policies by a part of the literature. However, and controversially, another stream of argumentation regards these activities as being aimed at advancing the reach of market forces. To fully grasp the ambiguous nature of the social activities of business, in this paper I provide an account of affirmative as well as of critical interpretations of these activities throughout the history of modern capitalism. On this basis, the power of critique to disentangle the diverse motivations that underlie the social engagement of business is highlighted as a condition for facilitating a role of business in society that balances economic and social considerations.
Keywords: POLANYI, Karl, 1886-1964; business ethics; capitalism; public goods; research; social responsibility of business; value creation; welfare state

Neo-pluralist political science, economic sociology and the conceptual foundations of the comparative capitalisms literatures - Bruff, Ian; Hartmann, Eva (Capital & Class, 2014)
In this paper, we critically assess two of the key conceptual foundations for the comparative capitalisms (CC) literatures, neo-pluralist political science and economic sociology, in order to identify more clearly the deep intellectual roots of these literatures. Principally, we focus on how the strengths of neo-pluralism and economic sociology – their attention to detail in considering the huge range of ‘types’ of capitalism that exist across the world – come at a high price. Put briefly, the redefinition of ‘capitalism’ as ‘the economy’ concentrates research agendas on the specific political and social conditions found across the world, leaving ‘the economy’ relatively untouched. In consequence, ‘capitalist diversity’ is quickly, and often silently, equated to ‘political diversity’ or ‘social diversity’. As such, a key weakness of CC scholarship, identified by various authors in this Capital & Class special issue – that it does not provide a satisfactory theoretical understanding of capitalist societies – is a problem that runs deeper than the limitations that can be observed in contemporary debates. The implications of our argument are discussed in the conclusion.
Keywords: capitalism; capitalist diversity; comparative capitalisms; economic sociology; neo-pluralism; political economy

Indigenous Development and the Cultural Captivity of Entrepreneurship - Peredo, Ana María; McLean, Murdith (Business & Society, 2013)
This article argues that thinking about entrepreneurship as a potential instrument for relief from endemic poverty and disadvantage, especially among the Indigenous, has all too often been captive to a concept of entrepreneurship that is built out of constrained economic and cultural assumptions. The authors develop this argument from a critical discussion of contributions by Karl Polanyi and Robert Heilbroner. The result is that approaches to venture have been encouraged that are sometimes a poor fit for the circumstances of those they are meant to benefit, and other forms that could have considerable promise have gone unexplored. This article outlines some features of Indigenous culture and build on the analysis of David Harper to construct an improved notion of entrepreneurship that allows for these distinctive features. The article concludes that research and policy making concerning entrepreneurship as an instrument of development among the Indigenous need to be undertaken with this reconstructed understanding of entrepreneurship that is a better fit for the realities of Indigenous culture.
Keywords: HEILBRONER, Robert; Indigenous development; Indigenous peoples; POLANYI, Karl, 1886-1964; cultural diversity; entrepreneurship; entrepreneurship and culture; poverty

The political economy of public sector trade union militancy under Keynesianism: The case of local government - Gill-McLure, Whyeda (Capital & Class, 2013)
Public service labour’s distinctiveness is insufficiently understood or recognised; and in its ad hoc growth under liberal ideologies of state intervention (those of Mill and Keynes), it has been treated both as if it were and were not public service labour. This paper teases out some of the crucial links between liberal ideologies of state intervention and the social praxis of public service unionism, outlining the latter’s historical struggle against this paradoxical treatment, which culminated in 1970s militancy. The paper supports this argument with a Marxist analysis of public sector labour, drawing on Polanyi’s ‘double-movement’ to understand the limitations of liberal ideologies of state intervention.
Keywords: Marxist analysis; civil service; distinctiveness of public service labour; double movement; ideology; labor process; labour process; liberalism; political economy; public sector union militancy

Union Campaigns as Countermovements: Mobilizing Immigrant Workers in France and the United Kingdom - Tapia, Maite; Turner, Lowell (British Journal of Industrial Relations, 2013)
In this article, we compare recent innovative union campaigns: the ‘sans papiers’ campaign in France and the ‘Justice for Cleaners’ campaign in the United Kingdom, both based on a sustained grass-roots mobilization of immigrant workers. Rather than focusing on the ‘usual suspect’ explanatory factors, such as contrasting national settings, union power structures or traditions, our cross-national comparison highlights important underlying similarities in unions' strategic responses to a growing precarious immigrant workforce. In the absence of established channels of representation, both unions decided to act like social movements fighting for social protection. Using Polanyi's framework, we view both case studies as examples of countermovements against heightened levels of global liberalization and precarious employment.
Keywords: comparative labour; countermovement; human resources; international labour; unions

From Pollyanna to the Pollyanna Principle. A Response to Michael Burawoy's 'From Polanyi to Pollyanna: The False Optimism of Global Labour Studies' - Caspersz, Donella (Global Labour Journal, 2010)
Keywords: BURAWOY, Michael; labor studies; labour studies; pollyanna principle

Industrial Relations Today: Reining in Flexibility - Streeck, Wolfgang (Economics, Management & Financial Markets, 2009)
The paper was presented as a keynote lecture at the 10th anniversary of the Amsterdam Institute for Advanced Labour Studies (AIAS) in April 2008. It surveys the trajectory of scholarly work on labor after 1945, from its initial emphasis on rights of industrial and social citizenship to its present preoccupation with "flexibility" and "flexicurity." It recalls the dissolution of the "Fordist" compromise in the 1970s and the subsequent gradual expansion of markets as the dominant mechanism for the allocation of life chances and the governance of society. Marketization encountered surprisingly little resistance, in real life as in the evolving conceptual apparatus of scholarly work. Liberalization proceeded and continues to proceed regardless of the social dislocations it causes, on a scale wholly unimaginable and indeed unacceptable under the postwar settlement. The paper ends with speculation on what if at all might be the forces today that could trigger a Polanyian counter-movement to the progress of capitalist social and economic relations. In particular it discusses whether demographic change, in terms of both a declining birth rate and increasing life expectancy, might bring about a new wave of market-containing social policy.
Keywords: corporate growth; countermovement; industrial relations; international economic relations; labor laws & legislation; labour laws & legislation; socioeconomics; welfare economics

Paper assets, real debts: An ecological‐economic exploration of the global economic crisis - Kallis, Giorgos; Martinez‐Alier, Joan; Norgaard, Richard B. (Critical perspectives on international business, 2009)
Purpose – This paper sets out to investigate the potential contribution of the inter‐disciplinary field of ecological economics to the explanation of the current economic crisis. The root of the crisis is the growing disjuncture between the real economy of production and the paper economy of finance. Design/methodology/approach – The authors trace the epistemological origins of this disjuncture to the myths of economism – a mix of academic, popular and political beliefs that served to explain, rationalise and perpetuate the current economic system. Findings – The authors recommend ending with economism and developing new collective and discursive processes for understanding and engaging with ecological‐economic systems. Originality/value – The authors embrace the notion of sustainable de‐growth: an equitable and democratic transition to a smaller economy with less production and consumption.
Keywords: commodification; commodification of nature

Globalization, inequalities and the “Polanyi problem” - Śliwa, Martyna (Critical perspectives on international business, 2007)
The purpose of this paper is to contribute to the debate on the consequences of globalization, in particular the increasing disparity between the wealth of nations and individuals in society. It discusses mechanisms which lead to perpetuation and reinforcement of the situation in which, despite being characterized by inequalities and fragmentation, societies remain by and large cohesive and stable. This article engages with the so-called “Polanyi problem” and with Polanyi’s and other authors’ responses to it. In the discussion, the analytical approach is adopted by reference to Aldous Huxley’s Brave New World, in particular his concept of soma. Using the metaphor of soma, developed into four interrelated dimensions, illustrations of social and organizational processes, which ensure sustainability of, and cohesion within, a society based on inequality and fragmentation, are indicated. It is argued that the existence of stratified societies, and inequalities of wealth within and between them, is accompanied by phenomena which support and sustain them. Drawing upon literary fiction can offer valuable insights into issues pertinent to contemporary academic debate. Engagement with Huxley’s work provides an alternative way of contributing to the globalization debate and, in particular, to the literature addressing the so-called “Polanyi problem”.
Keywords: Brave New World (book); HUXLEY, Aldous; Polanyi problem; distribution of wealth; globalization; international business; society; soma

Society Must Be Protected - Turner, Mandy (Journal of Corporate Citizenship, 2007)
The multiple ways in which multinational corporations, financial and commodity markets and global trade feed into today's civil wars have recently become a key policy concern of the international community. Over the past five years, a number of initiatives have been launched, aimed at controlling the trade in conflict goods, ensuring good resource governance, advocating corporate social responsibility and promoting conflict-sensitive business practices. This article assesses these initiatives through the lens of Karl Polanyi's conception of the 'double movement', i.e. that capitalism automatically provokes protectionist impulses. It assesses the spaces created by neoliberal globalisation for illicit economic activity and conflict entrepreneurs, the relationship between the economy and conflict, and initiatives aimed at reducing conflict 'triggers'. It concludes that, in addition to the tension between commodification and social protection, there is another tension at work: between those who call for tough mandatory policies and those who promote best-practice guidelines.
Keywords: Polanyi; business and conflict; capital market; commodification; corporate social responsibility; corruption; international business enterprises; international trade; protectionism; sanctions; social protection; social responsibility of business

The state we are in: insights from autopoiesis and complexity theory - Gregory, Amanda (Management Decision, 2006)
Purpose - Following Polanyi, this paper aims to suggest that the Industrial Revolution marked a break-point between pre-industrial society (characterised by integration) and industrial society (characterised by differentiation). Design/methodology/approach - As a conceptual paper, the focus is on drawing out the implications of Luhmann's application of the theory of autopoiesis to industrial society. This discussion leads to critical reflection on the state we are in and the active role we can each play in bringing about change. Findings - Differentiation, without an overall co-ordination and control function within society, has led to the sub-systems (and organisations) becoming self-serving or pathologically autopoietic. Society has a capacity for self-observation, through such mediums as the mass media. Alarm at the apparent increasing rate of change in both social and ecological systems reported by the mass media appears to be drawing us towards a second break-point. The outcome of this revolution, should it come about, is impossible to predict but descent into a new "dark age" is an option as is the re-integration of economic activity with social, religious and political functions. Luhmann's autopoiesis provides a convincing explanation for how society is structured and observing the implications of this. The role of the mass media as an observing system and in bringing information about change to society's attention is emphasised. Practical implications - The paper seeks to provide an explanation for how society is structured and demonstrate how society appears to be passively observing the implications of this. Proposals for both restructuring and the actions we, as active citizens and organisational members, can take to redress our current state are advanced. Originality/value - The paper brings together ideas from a diverse range of fields (including autopoiesis, complexity theory, and systems) and applies them to a highly significant topic.
Keywords: autopoiesis; complexity theory; economic history; industrial revolution; mass media; social history; social systems

Changing employment protection systems : Karl Polanyi's "Double Movement" and the evolution of federal labour standards in Australia 1979 to 2000 - Michelotti, Marco (Association of Industrial Relations Academics of Australia and New Zealand, 2004)
Yes
Keywords: Australia; double movement; industrial relations; labour standards

Our Obsolete Marketing Mentality: George Fisk, Meet Karl Polanyi - Benton, Raymond (Journal of Macromarketing, 2021)
Marketing in general can have greater influence if a new, yet old, perspective on marketing is adopted—something akin to the original orientation of marketing. Adopting George Fisk’s definition of marketing and marrying it with notions derived from the institutional economist Karl Polanyi is proposed. The histories of marketing thought and of institutional economics are reviewed to demonstrate their affinity and similar origins. Fisk’s conceptualization of marketing as societies’ provisioning systems is shown to correspond with Polanyi’s conceptualization of economies as instituted processes, admitting more than the market and the state as ways economies have historically and cross-culturally integrated with society. The obsolete marketing mentality is that marketers, including macromarketers, are overly fixated on the market and ignore or overlook alternatives. The Fisk/Polanyi orientation will attract macromarketers interested in marketing and development, critical marketing, sustainability, alternative economies, and those interested in the long-term prospects of macromarketing. Adopting this old, but new, framework will connect the past with the future, permit macromarketers make a mark on a larger intellectual landscape and serve to invite scholars in this larger landscape to engage with macromarketing.
Keywords: Future of Macromarketing; George Fisk; German Historical School; History of Economic Thought; Institutional Economics; Karl Polanyi; Marketing and Economics; history of marketing thought; macromarketing

Karl Polanyi on strategy: The effects of culture, morality and double-movements on embedded strategy - Faulconbridge, James R.; Muzio, Daniel (Critical Perspectives on Accounting, 2020)
Karl Polanyi is arguably one of the most significant economic sociologists. At first glance the links between Polanyi’s ideas about markets, society and institutions and strategy may not be obvious. However, there is a hereto unrecognised link between recent writing about institutions and strategy and Polanyi’s work. In this paper we, therefore, chart how, when recognised, these links reveal that Karl Polanyi’s work might provide new ways of thinking about strategy. Our over-riding claim is that Polanyi’s ideas reveal the importance of considering how strategies are defined, responded to, and ultimately rendered effective or ineffective in ways that are determined by relationships between markets, the state and society. It is thus crucial to understand strategy as embedded, this implying consideration of a strategy’s legitimacy in economy and society as an instituted process at any particular place and time. This also implies wider political questions about strategy in society and the extent to which strategists need to be aware of the ‘double movement’ Polanyi discusses and ensure strategies serve the interests of society as well as those of the market.
Keywords: Double movement; Globalization; Law firms; Polanyi; Strategy

Commodification & countermovement: community-supported agriculture (CSA): a case study in Minas Gerais, Brazil - Matzembacher, Daniele Eckert; Meira, Fabio Bittencourt (Organizações & Sociedade, 2020)
The conventional way of producing and distributing food is based on the use of agrochemicals, fertilizers, industrial fertilizers and other techniques from the Green Revolution, with increasing dependence on financial-industrial capital, which implies the intensification of the agriculture commodification. The object of this study was the emergence of modes of organization resisting this trend. Based on the theoretical reference of Karl Polanyi (2012a, 2012b), a case study was developed in a Community-Supported Agriculture (CSA) initiative. It is a movement that resituates agricultural production through the principles of fair trade, agroecology and the use of short supply chains, which bring production and consumption closer together. The result is a better nutritious quality food at affordable and fair price. The analysis of the CSA Alfa case points to the coexistence of different principles of regulation, in a combination of mercantile exchange and reciprocity. According to the proposition by Karl Polanyi, the economic activity is shown to imbricate with the social aspect, of which friendship, tolerance, fidelity and commitment establish a community ethos around food. The CSA seems to manifest a countermovement to the commodification by enhancing the relative autonomy of individuals that elevates the social cohesion of the participating groups. Resumo A forma que se tornou convencional de produzir e distribuir alimentos baseia-se no uso de agroquímicos, adubos, fertilizantes industriais e de outras técnicas provenientes da Revolução Verde, com crescente dependência do capital financeiro-industrial. Isto significa a intensificação da mercantilização da agricultura. O problema que norteou esta pesquisa é a emergência de modos de organização resistentes a essa tendência. Com base no referencial teórico de Karl Polanyi (2012a, 2012b), construiu-se um estudo de caso cujo objeto é a agricultura sustentada pela comunidade, cujo acrônimo em inglês é CSA (community supported agriculture). Trata-se de um movimento que ressitua a produção agrícola pelos princípios do comércio justo e da agroecologia e uso de cadeias curtas que aproximam produção e consumo. O resultado é um alimento de qualidade nutritiva superior a preço acessível e justo. A análise do caso CSA Alfa aponta a coexistência de diferentes princípios de regulação numa combinação de troca mercantil e reciprocidade. Na esteira de Karl Polanyi, observa-se a atividade econômica imbricada ao social, daí que amizade, tolerância, fidelidade e comprometimento estabelecem um ethos comunitário em torno do alimento. A CSA parece manifestar um contramovimento à mercantilização ao potencializar a autonomia relativa dos indivíduos, o que eleva a coesão social dos grupos participantes.
Keywords: Karl Polanyi; commodification; community-supported agriculture; reciprocity; social cohesion

The Contemporary Relevance of Karl Polanyi to Critical Social Enterprise Scholarship - Roy, Michael J.; Grant, Suzanne (Journal of Social Entrepreneurship, 2020)
The importance of the work of Karl Polanyi to social enterprise scholarship is often maintained. However, explanations as to how and why his ideas are so relevant to the field are still relatively scarce. In this essay, we argue that engaging with Polanyi’s work directly, and Polanyian scholarship more widely, can provide a deep understanding of the underlying assumptions within current social enterprise conceptualizations, and provide insights into how the relative positioning of market and society may be manipulated to maintain hegemonic positions. Three of Polanyi’s key concepts are considered and discussed in turn: the ‘substantive economy’, the notion of ‘embeddedness’, and his ‘double movement’ thesis. The contemporary relevance of each concept, and the implications for future research, are presented and discussed, with a view to providing a platform from which to pursue a reinvigorated, emancipatory critical research agenda.
Keywords: Polanyi; Social enterprise; critical research; critical social enterprise scholarship; double movement; economic sociology; embeddedness; social business; social enterprise; social innovation; substantive economy